EVALUASI PELAKSANAAN PROGRAM PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE (P2DBD) DI PUSKESMAS MOJOSONGO KABUPATEN BOYOLALI TAHUN 2018 - Faizah, Anis; Suryawati, Chrisardani; Fatmasari, Eka Yunila (Jurnal Kesehatan Masyarakat (Undip), 2018)
The development Dengue Hemorrhagic Fever (DHF) cases which tends to increase and their widespread distribution is one of the health problems that are of concern in Indonesia. Every year, Mojosongo Public Health Center's working area becomes an increasing number of DHF cases in Boyolali District. The local government has made a prevention and eradication program for DHF, but it is suspected that it has not succeeded in reducing cases of DHF. This study aims to evaluate the execution of the DHF Control Program seen from the input, process, and output variables. This study is a qualitative study using a depth interview method to 12 informants and this study observes on the sub-variables such as facilities, methods, and time. The result of the study on the input variable shows enough power availability but it is constrained from the scheduling of activities and the official report has yet done on every program execution activity. Process variable shows that PSN activities have not done in implemented optimally and there is a delay when dropping the abate powder from District Health Office (DHO) which often received in a state of expiration. Output variable from 5 indicators DHF Control Program is found that 1 indicator has not reached the target which ABJ in Mojosongo Health Center is only 67% with the actual target is 95%. The suggestion given for the problems mentioned is DHO Boyolali expected to fix the abate powder distribution system so that there are no delays and could avoid the expiration dates. It is necessary for the health center to increase the coordination and the communication for all the organizer cadres, DHO, and across sectors for the continuity of the execution DHF Control Program activities, doing official report and accompanying with village government through jumantik cadres on the execution of PSN.